Tumor biology of non-metastatic stages of clear cell renal cell carcinoma; overexpression of stearoyl desaturase-1, EPO/EPO-R system and hypoxia-related proteins - Stoyanoff, Tania Romina (2016)
Fil: Stoyanoff, Tania Romina. Universidad Nacional del Nordeste. Facultad de Medicina; Argentina.